2022
DOI: 10.1371/journal.pone.0266107
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of the injected current targeting the P20/N20 source determines the efficacy of 140 Hz transcranial alternating current stimulation (tACS)-induced aftereffects in the somatosensory cortex

Abstract: Interindividual anatomical differences in the human cortex can lead to suboptimal current directions and may result in response variability of transcranial electrical stimulation methods. These differences in brain anatomy require individualized electrode stimulation montages to induce an optimal current density in the targeted area of each individual subject. We aimed to explore the possible modulatory effects of 140 Hz transcranial alternating current stimulation (tACS) on the somatosensory cortex using pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…only individual target location, but especially individual target orientation plays an important role as also investigated and proposed by Refs. [16,18,26,28e30,32] and recently also found in a tACS study over the somatosensory cortex [33]. A total stimulation current of 2 mA might also be important, as it was earlier assumed that due to the depth of the central sulcus not enough currents reach the target area Brodmann area 3b with 1 mA [7,11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…only individual target location, but especially individual target orientation plays an important role as also investigated and proposed by Refs. [16,18,26,28e30,32] and recently also found in a tACS study over the somatosensory cortex [33]. A total stimulation current of 2 mA might also be important, as it was earlier assumed that due to the depth of the central sulcus not enough currents reach the target area Brodmann area 3b with 1 mA [7,11].…”
Section: Discussionmentioning
confidence: 89%
“…Our individualized targeting and stimulation approach might thus help to better control tDCS experimental paradigms. Our approach is also interesting for tACS, where recent studies also showed that neuroimaging combined with electric field modeling is useful to explain inter-individual variability of stimulation effects [15,33].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 4, 2023. ; https://doi.org/10.1101/2023.01.04.522700 doi: bioRxiv preprint the topology and orientation of the electric fields relative to a given stimulation target [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, the topology and magnitude of individual electric fields have been reported to correlate with the strength of tACS-modulations of neuronal activity [23,46]. Thus, by using algorithmic optimization of individual stimulation montages, personalized tACS has the potential to increase control over the topology and orientation of the electric fields relative to a given stimulation target [47,48]. In addition, this approach allows the post-hoc analysis of the estimated electric fields in conjunction with behavioral or neurophysiological outcome measures of tACS [23,45,cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation